2019
DOI: 10.1037/apl0000382
|View full text |Cite
|
Sign up to set email alerts
|

Effects of range restriction and criterion contamination on differential validity of the SAT by race/ethnicity and sex.

Abstract: We illustrate the effects of range restriction and a form of criterion contamination (individual differences in course-taking patterns) on the validity of SAT scores for predicting college academic performance. College data facilitate exploration of differential validity’s determinants because they (a) permit the use multivariate range-restriction corrections to more accurately account for differential range restriction across subgroups and (b) allow for separate examinations of composite performance and speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…With respect to differential prediction, we were unable to find any large-scale research examining the potential for differential prediction using GRE data. There is, however, a large body of research examining and debating whether the SAT demonstrates differential prediction (e.g., Aguinis et al, 2010;Berry et al, 2011;Dahlke et al, 2019;Fischer et al, 2013;Mattern & Patterson, 2013). The general consensus from this research is that the SAT tends to overpredict undergraduate GPAs for Black students compared to White students and tends to underpredict undergraduate GPAs for female students compared to male students.…”
Section: Grementioning
confidence: 98%
“…With respect to differential prediction, we were unable to find any large-scale research examining the potential for differential prediction using GRE data. There is, however, a large body of research examining and debating whether the SAT demonstrates differential prediction (e.g., Aguinis et al, 2010;Berry et al, 2011;Dahlke et al, 2019;Fischer et al, 2013;Mattern & Patterson, 2013). The general consensus from this research is that the SAT tends to overpredict undergraduate GPAs for Black students compared to White students and tends to underpredict undergraduate GPAs for female students compared to male students.…”
Section: Grementioning
confidence: 98%
“…However, this is more a limitation of the GPA metric in general than of our study in particular. Dahlke et al (2019) recently investigated whether criterion contamination in the form of individual differences in course-taking choices could explain White-minority differential validity of the SAT. They found that White–Black and White–Hispanic differential validity disappeared after controlling for differences in students’ course-taking choices.…”
Section: Discussionmentioning
confidence: 99%
“…These data were nonrandomly sampled by virtue of being collected from schools that used the SAT as a selection device and that consented to provide students’ grade data to the College Board for research purposes. The database we analyzed has been used in other published research (e.g., Beatty et al, 2015; Dahlke et al, 2018, 2019; Higdem et al, 2016; Kostal et al, 2015; Shewach et al, 2017; Yu et al, 2016), but the present study reports unique analyses of these data and draws novel insights.…”
Section: Methodsmentioning
confidence: 99%
“…This lack of research is surprising, given that Landers and Behrend’s (2015) discussion of convenience samples in organizational research emphasized range restriction as an inevitable issue across all convenience samples. Range restriction – when a sample’s variance is smaller than the variance in the target population – can limit generalizability, resulting in weaker correlations between variables of interest (Dahlke et al, 2019; McAbee & Oswald, 2017; Sackett & Yang, 2000).…”
Section: Scale Mean and Variance Differencesmentioning
confidence: 99%